2017
DOI: 10.1016/j.acap.2017.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Home Sweet Home: Parent and Home Environmental Factors in Adolescent Consumption of Sugar-Sweetened Beverages

Abstract: OBJECTIVE Sugar-sweetened beverages (SSBs) are key contributors to obesity among youth. We investigated associations among parental and home-related factors (parental attitudes and consumption; home availability) regarding three types of SSBs—soda, sports drinks, and fruit-flavored drinks—with consumption of each type of SSB in a general school-based sample of adolescents. METHODS Data were collected across three school semesters, from 2009–2011. A total of 1,313 seventh-grade student-parent dyads participat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
50
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 33 publications
(43 reference statements)
6
50
0
Order By: Relevance
“…Within the home environment, factors such as the availability and accessibility of SSBs, family meals, parental modelling, parenting practices and family food rules have been positively correlated with the intake of SSBs among children and adolescents living in developed countries (Grimm et al 2004;van der Horst et al 2007;Bere et al 2008;Haerens et al 2008;Ezendam et al 2010;Verzeletti et al 2010;Tak et al 2011;Hebden et al Electronic supplementary material The online version of this article (https://doi.org/10.1007/s10389-018-0993-6) contains supplementary material, which is available to authorized users. Van Lippevelde et al 2013;Bogart et al 2017). These findings provide an important insight into the factors that influence SSB intake at home in developed countries, mostly in Europe.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Within the home environment, factors such as the availability and accessibility of SSBs, family meals, parental modelling, parenting practices and family food rules have been positively correlated with the intake of SSBs among children and adolescents living in developed countries (Grimm et al 2004;van der Horst et al 2007;Bere et al 2008;Haerens et al 2008;Ezendam et al 2010;Verzeletti et al 2010;Tak et al 2011;Hebden et al Electronic supplementary material The online version of this article (https://doi.org/10.1007/s10389-018-0993-6) contains supplementary material, which is available to authorized users. Van Lippevelde et al 2013;Bogart et al 2017). These findings provide an important insight into the factors that influence SSB intake at home in developed countries, mostly in Europe.…”
Section: Introductionmentioning
confidence: 74%
“…Previous research on adolescents' proximal context, such as family, school and peers, has suggested a positive association between the home and school environments and SSB intake (van der Horst et al 2008;Ezendam et al 2010;Shi 2010;Tak et al 2011;Bogart et al 2017). Within the home environment, factors such as the availability and accessibility of SSBs, family meals, parental modelling, parenting practices and family food rules have been positively correlated with the intake of SSBs among children and adolescents living in developed countries (Grimm et al 2004;van der Horst et al 2007;Bere et al 2008;Haerens et al 2008;Ezendam et al 2010;Verzeletti et al 2010;Tak et al 2011;Hebden et al Electronic supplementary material The online version of this article (https://doi.org/10.1007/s10389-018-0993-6) contains supplementary material, which is available to authorized users.…”
Section: Introductionmentioning
confidence: 99%
“…All these factors should be considered by policy-makers investigating ways to increase the effectiveness of the SSB tax in Mexico. Despite not having been discussed with participants in this sample, factors such as heavy marketing and publicity regulations (43,44) , parental and peer modelling (40,45) , leisure activities (46) , the environment (i.e. proximity to shops, home availability) (47) and scarcity of potable water in schools (48) and public spaces (49) might influence beverage choices among young people, and could therefore also influence adolescents' perceptions and acceptance of SSB taxation.…”
Section: Discussionmentioning
confidence: 99%
“…Parental influences shape children’s eating behaviors from early in childhood through the availability and accessibility of food in the home and by restriction and promotion of certain foods and amounts . Parents are considered to be the gatekeepers of food up until early adolescence and continue to have responsibility for feeding , although adolescents increasingly make independent DI choices .…”
Section: Introductionmentioning
confidence: 99%
“…Despite the large literature on the positive effects of PGM, little attention has been paid to its associations with adolescent weight‐related behaviors and weight status. We are aware of only three studies, but these show mixed findings: one study found that having no curfew, an indication of less monitoring, was associated with a higher likelihood of retaining obesity from adolescence into young adulthood ; a second study showed no association between parental monitoring of adolescent activities and adolescent obesity ; and a third study reported that monitoring was associated specifically with lower consumption of sugar‐sweetened beverages , a commonly targeted DI behavior when attempting to reduce obesity. The current study attempts to enhance understanding of whether and how PGM plays a role in adolescent weight status by examining its relationship with weight‐related healthy behaviors, such as healthy DI and PA, and unhealthy behaviors, such as unhealthy DI and screen time.…”
Section: Introductionmentioning
confidence: 99%